SISTEM ADMINISTRASI PELAYANAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BENGKULU - Zulita, Leni Natalia; Kanedi, Indra (UNIVED Press, 2011)
The main purpose of holding and of this study was to create a System Administration Citation Reports Birth Certificate in the Department of Population and Civil Registration Bengkulu city with the method of system development using Visual Basic programming language. Data collection methods used in this study is observation, interviews and literature. The software used to build the system INIA dalah Programming Languages Visual Basic 6.0 and the results obtained are able to provide fast and precise output.The results of this study are in the form of System Administration Birth Certificate Citation Reports on Population and Civil Registration Department of the city of Bengkulu with system development methods. From the main menu and there is a system there are two input data that is input data requirements and data input and two menus quote edit data ie the data edit and edit data requirements quotes and menus report containing evidence report quotes deed, deed citation monthly report, the report quotes deed annually and report damage blank. From this discussion it can be concluded that the System Administration Citation Reports Birth Certificate in the Department of Population and Civil mutilations Bengkulu city with system development method is replacing the old system with a new system which is a program that is specific.